Andalusian communication offices on X (Twitter): strategic analysis of their digital presence. - Castillero-Ostio, Elizabet; Almansa-Martínez, Ana María; Serna-Ortega, Álvaro (Visual Review, 2025)
Social media isessential for the digital positioning of organisations, their engagement with audiences, and the construction of their visual identity. This study examines the strategic management of Andalusian communication offices on X (Twitter), analysing their digital presence across three dimensions: profile, activity, and interaction. Employing a quantitative approach, the study analyses the accounts of 653 organisations. The research concludes that communication offices have professionalised their presence on X, albeit with notable differences depending on the type of organisation. The findings suggest the need to prioritise interaction over the volume of posts.
Keywords: Relaciones públicas; Redes sociales en internet; Communication offices; X/Twitter; Public relations; Communication; Andalusia; Social media; Organisations